Daily Activity and Honey Production Patterns of Tetragonula laeviceps Smith (Hymenoptera: Apidae) During the Wet and Dry Seasons - Suhri, Andi Gita Maulidyah Indraswari; Retnoaji, Bambang; Mustamin, Yusdar; Kahono, Sih (Universitas Gadjah Mada, 2024)
Honey production by stingless bees is closely related to the foraging activities of worker bees, particularly nectar foraging. The urgency of this study stems from the community's need for adequate understanding and information on honey production which can vary due to various factors, such as forage and season. The purpose of this study was to determine the extent to which foraging activity affects the amount of honey produced by T. laeviceps during the rainy and dry seasons. The focal sampling method was used to observe foraging behaviour and the acetolysis method was used to observe pollen. The abiotic factors were measured through direct observation. Honey production was observed as a result of foraging behaviour and variations in abiotic factors. In SPSS v27 software, data from foraging behaviour observations were analysed using one-way ANOVA followed by Tukey's test with 95% confidence level and interpreted in tables and figures. Multiple linear regressions and Pearson’s correlations were used to test the relationship between abiotic variables and bee return to hive behaviour. All honey volume data were collected, averaged, and evaluated using bar charts. Based on these results, the amount of honey produced by T. laevicepsin the dry season was significantly higher than that produced during the wet season. This was because the number of bees actively foraging was also higher in the dry season (June-August) which was strongly influenced by temperature and light intensity (p > 0.05). In addition, the number of flowering plants available for harvest during the dry season was higher than that during the rainy season. The results of this study can be used as a reference by beekeepers to determine the appropriate time to harvest honey. Information on the types of forage plants identified in this study can provide information on bee preferences in making choices related to forage plants.